Fermentation of pseudocereals quinoa, canihua, and amaranth to improve mineral accessibility through degradation of phytate. (5th June 2019) - Castro‐Alba, Vanesa; Lazarte, Claudia E; Perez‐Rea, Daysi; Carlsson, Nils‐Gunnar; Almgren, Annette; Bergenståhl, Björn; Granfeldt, Yvonne
Abstract: BACKGROUND: Pseudocereals are nutrient‐rich grains with high mineral content but also phytate content. Phytate is a mineral absorption inhibitor. The study's aim was to evaluate phytate degradation during spontaneous fermentation and during Lactobacillus plantarum 299v® fermentation of quinoa, canihua, and amaranth grains and flours. It also aimed to evaluate the accessibility of iron, zinc, and calcium and to estimate their bioavailability before and after the fermentation of flours with starter culture. Lactic acid, pH, phytate, and mineral content were analyzed during fermentation. RESULTS: Higher phytate degradation was found during the fermentation of flours (64–93%) than during that of grains (12–51%). Results suggest that phytate degradation was mainly due to endogenous phytase activity in different pseudocereals rather than the phytase produced by added microorganisms. The addition of Lactobacillus plantarum 299v® resulted in a higher level of lactic acid (76.8–82.4 g kg −1 DM) during fermentation, and a relatively quicker reduction in pH to 4 than in spontaneous fermentation. Mineral accessibility was increased (1.7–4.6‐fold) and phytate : mineral molar ratios were reduced (1.5–4.2‐fold) in agreement with phytate degradation (1.8–4.2‐fold) in fermented flours. The reduced molar ratios were still above the threshold value for the improved estimated mineral bioavailability of mainly iron. CONCLUSION: Fermentation proved to be effective for degrading phytate in pseudocereal flours, but less so in grains. Fermentation with Lactobacillus plantarum 299v® improved mineral accessibility and estimated bioavailability in flours. © 2019 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.